THERAPEUTIC POTENTIAL OF CREATINE IN PSYCHIATRY: FROM NEUROBIOLOGY TO CLINICAL APPLICATIONS - Szymon Gnitecki; Jakub Wasiak; Kacper Zielonka; Bartosz Dądela; Marcin Markowski; Natalia Śliwa; Dominika Jakubowska; Eliza Kawalska; Szymon Janczura; Maciej Borowski (International Journal of Innovative Technologies in Social Science, 2025)
Mental disorders such as depression, bipolar disorder, schizophrenia, and anxiety are difficult to treat due to their complex neurobiological substrates. Traditional treatments, including pharmacotherapy and psychotherapy, are poor in alleviating symptoms in the majority of patients, where other forms of intervention have been sought. Creatine supplementation, which has been shown to previously improve sports performance, has been looked upon in this context as a form of treatment. Creatine plays a critical role in cellular energy metabolism, particularly in the brain, where it may be useful in the alleviation of energy deficits, oxidative stress, and mitochondrial dysfunction. This review consolidates available information on mechanisms of creatine action, clinical trials, and therapeutic implications in psychiatric disorders and discusses its well-established application in sports with its physiological and molecular effects. Specifically, we address creatine’s influence on energy metabolism, neuroprotection, neurotransmitter modulation, and synaptic plasticity. The evidence shows creatine to be a potentially valuable adjunctive treatment, particularly in depression and affective disorders; however, more research is called for to elucidate its whole therapeutic value and develop optimal dosing regimens in heterogeneous patient populations.